Anti-money laundering governance in the Philippines: legal foundations, institutional dynamics and policy challenges - Blanco, Dennis Vicencio (2017)
Effective anti-money laundering governance is essential in all countries with banks and other financial institutions which could be, or already are, the targets of money laundering aimed at making the proceeds of illegal activities appear to be clean and legitimate. The Philippines is no exception, with the government having taken some important initiatives but needing to do more to meet significant international expectations and standards. Accordingly, this article assesses the country's anti-money laundering governance in terms of its legal foundations, institutional dynamics and policy challenges, which all point to a need for ongoing review and reform. - Reproduced.
Keywords: Money - Philippines; Money